Federal Practitioner 2022
DOI: 10.12788/fp.0330
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expansion and Veterans’ Reliance on the VA for Depression Care

Abstract: Background: In 2001, before the Affordable Care Act (ACA), some states expanded Medicaid coverage to include an array of mental health services, changing veterans' reliance on US Department of Veterans Affairs (VA) services. Methods: Using Medicaid and VA administrative data from 1999 to 2006, we used a difference-in-difference design to calculate shifts in veterans' reliance on the VA for depression care in New York and Arizona after the 2 states expanded Medicaid coverage to adults in 2001. Demographically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…They were the lowest for VA enrollees who had a medical condition related to their military service. Both findings are in line with research on past Medicaid expansion 12–14 . Veterans with service‐connected conditions may feel more closely connected to the VA due to the nature of their conditions.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…They were the lowest for VA enrollees who had a medical condition related to their military service. Both findings are in line with research on past Medicaid expansion 12–14 . Veterans with service‐connected conditions may feel more closely connected to the VA due to the nature of their conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies found VA usage remained relatively steady among VA enrollees who became eligible for Medicaid, though usage varied by health conditions 10,11 . We have shown that pre‐ACA Medicaid expansions in Arizona and New York correlated with increased dual enrollment and reductions in the VA proportion of total care, though not the amount of care 12–14 . More recent research found expansion was associated with a 2.5 percent reduction in VA hospitalizations in 32 states 15 .…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations